Sensing Techniques for Food Safety and Quality Control. - Lu, Xiaonan (Food Chemistry, Function and Analysis ;, 2017)
Providing an updated summary of the application of different types of sensors for the analysis of food safety and quality, this book discusses the core principles, current research status, challenges and successful examples for each technology. -- Resumé vydavatele